2013
DOI: 10.1534/genetics.112.144535
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Derived Genotype Probabilities to Discover Significant Dominance Effects for Milk Production Traits in Dairy Cattle

Abstract: The estimation of dominance effects requires the availability of direct phenotypes, i.e., genotypes and phenotypes in the same individuals. In dairy cattle, classical QTL mapping approaches are, however, relying on genotyped sires and daughter-based phenotypes like breeding values. Thus, dominance effects cannot be estimated. The number of dairy bulls genotyped for dense genome-wide marker panels is steadily increasing in the context of genomic selection schemes. The availability of genotyped cows is, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The development of dense SNP panels offered new opportunities for detection and use of dominance at individual loci. Boysen et al [21] reported that significant dominance effects on milk production traits in cattle were identified in a WGAS [21]. …”
Section: Resultsmentioning
confidence: 99%
“…The development of dense SNP panels offered new opportunities for detection and use of dominance at individual loci. Boysen et al [21] reported that significant dominance effects on milk production traits in cattle were identified in a WGAS [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Different genetic effects (e.g. additive, dominance, and epistasis) are also expected to have influence on complex traits464748, however most of the association studies ignore dominance and epistasis effects4950. Full model approach estimated around 11.24% heritability for dominance and epistasis effects and 10.21% heritability for ethnic specific dominance and epistasis effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the genetic improvement of crossbreeding performances implies that non-additive genetic variance could be taken into consideration. Accounting for non-additive effects in GEBV predictions may be theoretically and computationally complicated and additional studies are needed to dissect and take advantages from these genetic components (Boysen et al 2013). Their correct estimation would likely require the use of raw data as dependent variable and their practical use would be probably limited to planned mating.…”
Section: Perspectives Of the Genomic Selection In Pigs And Concludingmentioning
confidence: 99%